If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -3 = 4x + 39 Reorder the terms: -3 + 8x = 4x + 39 Reorder the terms: -3 + 8x = 39 + 4x Solving -3 + 8x = 39 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -3 + 8x + -4x = 39 + 4x + -4x Combine like terms: 8x + -4x = 4x -3 + 4x = 39 + 4x + -4x Combine like terms: 4x + -4x = 0 -3 + 4x = 39 + 0 -3 + 4x = 39 Add '3' to each side of the equation. -3 + 3 + 4x = 39 + 3 Combine like terms: -3 + 3 = 0 0 + 4x = 39 + 3 4x = 39 + 3 Combine like terms: 39 + 3 = 42 4x = 42 Divide each side by '4'. x = 10.5 Simplifying x = 10.5
| -70+2x+8x=70 | | (2y+20)= | | f(x)=x^2+11x+0 | | 63x-35= | | 3x^2-2x-100=0 | | r^16+5=11 | | 45x=25-5y | | 4x+3y=y+8 | | -4n+16=116 | | 2100=x*60 | | 5y=25-45x | | 2h(4h+3)= | | 18y-18=18 | | -w^7-2=19 | | log(x+6)=log(8x)-log(3x+2) | | 6x+10+4x+40=180 | | 4n+16=116 | | 2y+10-y=-7 | | -(2-3b)=2(3b-4) | | 4n+16=16 | | 4(2x-y)+11=8x-13 | | 3a+5=2a+17 | | 6x+19=-30 | | 3x-9=5x+15 | | 14x-9=21+4x | | 3t+4t=51-8 | | (-5)+4=x-3 | | 3(u+3)=-6(4u-1)+9u | | (6x+40)-2x=(2x+116)-2x | | y-11=-17 | | (5x+10)-3x=(3x+36)-3x | | 6m-9=21 |